Neuronal satellitosis is a common finding in the avian brain. Issue 4 (4th July 2022) - Giglia, Giuseppe; Agliani, Gianfilippo; Lepri, Elvio; Baldoni, Erika; Gobbi, Marco; Ceccherelli, Renato; Gröne, Andrea; van den Brand, Judith M. A.; Mandara, Maria Teresa
ABSTRACT: Perineuronal or neuronal satellitosis is the term describing the presence of glial cells in the satellite space surrounding the neuronal perikaryon. Confusingly, this finding has been described both as a physiologic and pathologic condition in humans and animals. In animals, neuronal satellitosis has been described in mammals, as well as in avian species. For the latter, the authors wondered whether neuronal satellitosis is expressed in the normal telencephalon of different avian orders and families and whether this pattern in different species shows a specific brain-region association. For these aims, this study explored the presence of neuronal satellitosis in the major areas of the healthy telencephalon in wild and domestic avian species of different orders and families, evaluating its grade in different brain regions. Neuronal satellitosis was seen in the hyperpallium and mesopallium as areas with the highest grade. Passeriformes showed the highest grade of neuronal satellitosis compared to diurnal or nocturnal raptors, and Charadriiformes. To clarify the exact role of neuronal satellitosis in animals without neurological disease, further studies are needed. RESEARCH HIGHLIGHTS: Neuronal satellitosis is a common finding in the healthy avian telencephalon. Neuronal satellitosis is a species- and brain-region-associated finding in birds. Passeriformes have the highest grade of neuronal satellitosis.